2018
DOI: 10.1039/c7fo01489a
|View full text |Cite
|
Sign up to set email alerts
|

A novel PTP1B inhibitor extracted fromGanoderma lucidumameliorates insulin resistance by regulating IRS1-GLUT4 cascades in the insulin signaling pathway

Abstract: Insulin resistance caused by the overexpression of protein tyrosine phosphatase 1 B (PTP1B) as well as the dephosphorylation of its target is one of the main causes of type 2 diabetes (T2D). A newly discovered proteoglycan, Fudan-Yueyang Ganoderma lucidum (FYGL) extracted from Ganoderma lucidum, was first reported to be capable of competitively inhibiting PTP1B activity in vitro in our previous work. In the present study, we sought to reveal the mechanism of PTP1B inhibition by FYGL at the animal and cellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 41 publications
0
34
0
Order By: Relevance
“…Since this protein was found to be overexpressed in insulinsensitive peripheral tissues (fat, muscle) and in hepatic cells during insulin-resistant state, searching for PTP1B inhibitors has become an important area of research in the treatment of impairment of insulin transmission pathway. FYGL (Fudan-Yueyang G. lucidum extract) appears to be a promising substance showing PTP1B inhibitory activity with weak cell permeability and bioavailability [26,27].…”
Section: Irs Protein Nodementioning
confidence: 99%
“…Since this protein was found to be overexpressed in insulinsensitive peripheral tissues (fat, muscle) and in hepatic cells during insulin-resistant state, searching for PTP1B inhibitors has become an important area of research in the treatment of impairment of insulin transmission pathway. FYGL (Fudan-Yueyang G. lucidum extract) appears to be a promising substance showing PTP1B inhibitory activity with weak cell permeability and bioavailability [26,27].…”
Section: Irs Protein Nodementioning
confidence: 99%
“…38 Interestingly, FYGL was also shown to improve insulin-stimulated glucose uptake and activation of IRS-1, PI3K and AKT by blocking PTP1B activation in rat myoblast L6 cells. 38 Consistent with previous evidence, we found that infliximab also acts as PTP1B inhibitor by exerting the ability to improve insulin signalling pathway and consequently glucose homeostasis in 3T3L1 adipocytes exposed to TNF-alpha in vitro.…”
Section: Discussionmentioning
confidence: 98%
“…In this sense, Yi‐ming Ma and coworkers previously showed that CCF06240, a PTP1B inhibitor, restores insulin sensitivity in HFD‐fed mice and promotes phosphorylation of IRS‐1 in HepG2 cells in vitro . Similarly, a recent study reported a decrease in blood glucose and insulin resistance in ob/ob mice receiving Fudan‐Yueyang‐Ganoderma‐lucidum (FYGL), a proteoglycan with the ability to inhibit PTP1B . Interestingly, FYGL was also shown to improve insulin‐stimulated glucose uptake and activation of IRS‐1, PI3K and AKT by blocking PTP1B activation in rat myoblast L6 cells .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…IRS-1 and IRS-2 are widely distributed in mammalian tissue, while IRS-4 restricts its expression to the hypothalamus [85], these proteins are adapter molecules for the kinase activity of the phosphorylated insulin receptor, in turn phosphorylating the p85 regulatory subunit of phosphoinositide 3-kinase (PI3K). The phosphorylation of the latter induces a conformational change of this protein which leads to the binding of the catalytic subunit (p110) activating PI3K; once activated, this protein phosphorylates phosphatidylinositol-3,4-diphosphate (PIP2) into the second messenger phosphatidylinositol-3,4,5-triphosphate (PIP3) [86,87], and these lipid products induce the recruitment and the interaction of the protein kinase (PDK)-1 and serine/threonine-specific protein kinase (Akt). The activation of PDK-1 phosphorylates some isoforms of protein kinase C, such as PKCλ/ζ, which is responsible for phosphorylating vesicles that contain the glucose transporter type 4 (GLUT4), promoting migration and fusion with the cell surface, which increases glucose uptake as well as your metabolism [88] (Figure 6A).…”
Section: Insulin Resistance and Obesitymentioning
confidence: 99%